Some patterns of rhythm and harmony in kalumbu music - Davidson, Marjory (International Library of African Music, 1973)
In the 1965 issue of this Journal, I gave some details of the music and tuning of two Zambian kalumbu bows. In the present article I should like to discuss the musical patterns of some more examples of this type of music and to add pieces for the kalumbu which is found in the Eastern Province of Zambia.
Keywords: African Music